5-Substituted Flavones—Another Class of Potent Triplex DNA-Specific Ligands as Antigene Enhancers - Landy Gu; Nghia Tran; Vanessa M. Rangel; Mandeep Singh; Krege M. Christison; Geoff P. Lin-Cereghino; Liang Xue (Molecules)
In the field of drug development, the quest for novel compounds that bind to DNA with high affinity and specificity never ends. In the present work, we report the newest development in this field, namely, triplex DNA-specific binding ligands based on the 5-substituted flavone scaffold in our lab. Biophysical studies showed that the newly synthesized flavone derivatives (depending on the side chains) bind to triplex DNA with binding affinities better than or similar to 5-substituted 3,3′,4′,7-tetramethoxyflavonoids. These compounds selectively stabilize triplex DNA while having little effect on duplex DNA, as verified by various biophysical methods. A detailed structural analysis suggested that the binding of these compounds to triplex DNA depends on the type of amino groups in the side chains and the length of the side chains. Viscosity studies suggested that these ligands bind to triplex DNA via intercalation. A representative ligand, compound 4b, showed a positive inhibitory effect on the activity of a restriction endonuclease (DraI) via ligand-mediated triplex formation. Several of these compounds exhibited excellent cytotoxicity toward various cancer cell lines (HT-29, HCT116, and HL-60), as indicated by the MTT assay. The work presented here is part of a continued effort from our laboratory to explore the novel structural motifs of natural product flavonoids for the development of triplex-specific ligands as antigene enhancers.